Determinasi Potensi Kebangkrutan pada BPR di Jawa Tengah - Nuryani, Anum; Cahya, Fachreza Via (UNIVERSITAS DHARMAWANGSA, 2025)
The bankruptcy of Rural Banks (BPR) can have serious impacts, not only on their customers but also on the regional economy and the overall stability of the financial system. A high number of bankruptcies among BPRs may occur due to financial difficulties, forcing these banks to shut down. This study aims to analyze and examine the influence of Operating Expenses to Operating Income (BOPO), Non-Performing Loans (NPL), Credit Interest Rates (SKB), and Growth in Micro Lending (GML) on the potential for bankruptcy in BPRs located in Central Java. The population of this study consists of 258 conventional BPRs, with a sample of 142 BPRs observed over the 2020–2023 period, resulting in 567 observation data points. The data were analyzed using EViews software, employing panel data model estimation tests, model selection, classical assumption tests (multicollinearity and heteroskedasticity), correlation coefficients, determination coefficients, and hypothesis testing. The results show that the fixed effect model is the most appropriate, and partial hypothesis testing reveals that BOPO and SKB have a significant effect on bankruptcy potential. Simultaneously, BOPO, NPL, SKB, and GML have a significant effect on the potential for bankruptcy.